2022
DOI: 10.3171/2022.5.spine211468
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the AO Spine Sacral and Pelvic Classification System: a systematic review

Abstract: OBJECTIVE The purpose of this study was to describe the genesis of the AO Spine Sacral and Pelvic Classification System in the context of historical sacral and pelvic grading systems. METHODS A systematic search of MEDLINE, EMBASE, Google Scholar, and Cochrane databases was performed consistent with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify all existing sacral and pelvic fracture classification systems. RESULTS A total of 49 articles were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…1,2 Although many sacral classification systems have been previously proposed, most are mainly descriptive and limited in their assessment of sacral and pelvic morphology, and none have been adopted as a universal standard. [3][4][5][6] Therefore, in 2020, the Arbeitsgemeinschaft für Osteosynthesefragen (AO) Knowledge Forum Trauma published the AO Spine Sacral Injury Classification System. 7 The goal of the classification was to design a comprehensive system that could be easily and consistently applied by practitioners across different specialties to guide the treatment of these complex injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Although many sacral classification systems have been previously proposed, most are mainly descriptive and limited in their assessment of sacral and pelvic morphology, and none have been adopted as a universal standard. [3][4][5][6] Therefore, in 2020, the Arbeitsgemeinschaft für Osteosynthesefragen (AO) Knowledge Forum Trauma published the AO Spine Sacral Injury Classification System. 7 The goal of the classification was to design a comprehensive system that could be easily and consistently applied by practitioners across different specialties to guide the treatment of these complex injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the anatomical location of the sacrum, which connects the lumbar spine to the pelvis, sacral fractures lie at the intersection of the fields of spine and trauma and often require a multidisciplinary team for treatment 1,2 . Although many sacral classification systems have been previously proposed, most are mainly descriptive and limited in their assessment of sacral and pelvic morphology, and none have been adopted as a universal standard 3–6 . Therefore, in 2020, the Arbeitsgemeinschaft für Osteosynthesefragen (AO) Knowledge Forum Trauma published the AO Spine Sacral Injury Classification System 7 .…”
mentioning
confidence: 99%
“…zone I = through the sacral area (50% of cases with 5.9% of neurological lesion of the lumbosacral trunk); zone II = through the sacral foramen (34% of cases with 28.4% of sacral plexus lesions); zone III through the sacral canal (16% of cases with 56% of neurological lesion with partial or total cauda equina syndrome). Further studies have shown that the rate of neurological impairment was lower with 1.9% in zone I, 5.8% in zone II, and 8.6% in zone III ( 17 ). Gibbons defined the neurological impairment linked to sacral fracture ( 18 ).…”
Section: Which Classification Is Useful In Practice?mentioning
confidence: 95%
“…The AO defined a classification which integrates the sacral lesion and the pelvic lesion ( 17 ). This classification system introduces injury patterns in order of stability, while simultaneously taking into consideration the degree of neurological deficit; three types A, B, and C. Type A injuries have no impact on the stability of the posterior pelvic ring or spine, given their distant location from the weight-bearing axis.…”
Section: Which Classification Is Useful In Practice?mentioning
confidence: 99%
See 1 more Smart Citation